(untitled) (Педагогіка вищої та середньої школи, 2004)
The essence and elements of “vocal culture” notion are shown in this article. Particular attention is paid to the forming of future music teachers’ “vocal culture”. Some methodological recommendations, which influence on voice progress, are given. The development of professional experience in the context of music culture’s style peculiarity is considered.